2008
DOI: 10.1111/j.1439-0485.2008.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term patterns of sponge diversity on a rocky tropical coast: evidence of large‐scale structuring factors

Abstract: The importance of a long-term ecological perspective is well documented, yet long-term data are not widely available. This paper represents the first quantitative description of sublittoral sponge assemblages over long temporal scales (6 years) along the coast of the East Pacific Ocean (Mazatlan Bay), with the goal of describing their levels of intra-and inter-annual variability, and their relationship to changing environmental conditions. It was possible to detect an apparent short-term pattern (intra-annual)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 78 publications
1
47
1
1
Order By: Relevance
“…52 ind m -2 ) and richness (max. 6.1 species m -2 ) of sponges were comparable with those reported in rocky habitats (17.5 ind m -2 and 4.3 species m -2 , Bell and Carballo 2008;Carballo et al 2008) and Sargassum beds (23.9 ind m -2 and 4.8 species m -2 , Á vila et al 2010) of the region.…”
Section: Discussionsupporting
confidence: 84%
“…52 ind m -2 ) and richness (max. 6.1 species m -2 ) of sponges were comparable with those reported in rocky habitats (17.5 ind m -2 and 4.3 species m -2 , Bell and Carballo 2008;Carballo et al 2008) and Sargassum beds (23.9 ind m -2 and 4.8 species m -2 , Á vila et al 2010) of the region.…”
Section: Discussionsupporting
confidence: 84%
“…In the Ca rib be an, a long -term de cline (over 14 years) in abun dance and diver sity of a reef sponge com mu nity was linked to dis ease in Panama (Wulff 2006 b ) and increases in abun dance of X. muta over a 6 -yr pe riod were re lated to re cruit ment pulses in the Florida Keys (McMurray et al 2010). A study of a sub trop i cal rocky coast sponge assem blage in Mexico revealed short -term fl uctu a tions were cor re lated with sea sonal changes in lo cal wind pat terns and sed i ment de po sition, nested within large -scale an nual patterns re lated to the Southern Oscillation and Multivariate El Ni ñ o Southern Oscillation indi ces (Carballo et al 2008). Longer -term mon i tor ing of the sponge as sem blages at Hoga and Sampela are nec es sary in or der to de ter mine the cause of the ob served in crease in sponge abun dance and whether these increases are part of a long -term trend or shortterm sea sonal fl uc tu a tions.…”
Section: Discussionmentioning
confidence: 99%
“…A 14 year study of sponges on a shallow reef in Panama revealed a steady disappearance of sponge species over the study period possibily due to sponge disease [35]. The results of a six year study in Mexico found short-term and long term fluctuactions in sponge densities as a result of seasonal changes in wind patterns and large-scale structuring factors such as the El Niño Southern Oscillation [36]. These contrasting results indicate that the factors controling sponge densities are likely to vary on different reef systems.…”
Section: Fig (5)mentioning
confidence: 95%